Selective Red Cell Variables in Chippiparai Hound Breeds of Tamil Nadu- a Pilot Study in 30 Dogs - G.R.Baranidharan; S.Vairamuthu; S.Suba Priya; N.R. Senthil (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Globally, many clinico-pathologic differences between hounds and other breeds have been investigated and most of the research has been focused on differences in the hematologic values between the breeds and hematologic reference intervals for the Greyhounds, which have been recently published. However, our native hound, Chippiparai, closely resembles the morphological traits of the hounds and yet there are no published reports on the hematological parameters of the Chippiparai breed from Tamil Nadu. Hence, this study was carried out to investigate the red cell variables like Hemoglobin, Packed Cell Volume and RBC counts which were compared with that of non-hound breeds. Chippiparai hound dogs (n=30) and non-hound dogs (n=30) were selected amongst the dogs presented at Madras Veterinary College Teaching Hospital and various native hamlets. The Hb, PCV and RBC level sin the Chippiparai breeds were found to be higher which may probably be attributed to the need for appropriate oxygen supplementation under extreme climatic conditions, for running and hunting and probably as an inheritance from the other sight hounds. Also, these breeds can be recommended as good blood donors since a lesser volume of their transfused blood (with greater PCV) can increase the hematological parameters of the anemic recipient dog as compared to an equal volume of blood from the non-hound blood donors.